Optimisation of construction mode of residential houses based on the genetic algorithm under BIM technology - Liu, Sufang; Shi, Lei; Liu, Simian; Wang, Chuan (Applied mathematics and nonlinear sciences, 2023)
BIM technology is a breakthrough in the construction industry whose application is of great value, and the engineering design, engineering budget and cost control combined with BIM technology have been developed rapidly. Therefore, in this paper, BIM technology is adopted to optimise the construction mode, and the genetic algorithm is selected to solve the scheduling model of construction. By applying an interdisciplinary research method combined with computer science and technology, an intelligent optimisation model of construction can provide a new research perspective and technical method for the development of the construction industry.